Tectonic structure of Central-Western Attica (Greece) based on geophysical in vestigations-Preliminary results - Papadopoulos, T. D.; Goulty, N.; Voulgaris, N. S.; Alexopoulos, J. D.; Fountoulis, I.; Kambouris, P.; Karastathis, V.; Peirce, C.; Chailas, S.; Kassaras, J.; Pirli, M.; Goumas, G.; et al. (Bulletin of the Geological Society of Greece, 2007)
In an effort to investigate the deep geological structure in the broader area of central-western Attica, that suffered severe damage during the destructive Athens earthquake of September 7th, 1999, the Department of Geophysics-Geothermics of the Faculty of Geology and Geoenvironment of Athens University, in collaboration with the Geodynamic Institute of National Observatory of Athens and the Department of Geological Sciences of Durham University, carried out a combined geophysical survey. For the first time in Attica, seismic and gravity geophysical methods were applied along profiles, in such an extensive scale. Within the framework of this investigation the following tasL· were accomplished: a) Three (3) seismic lines of about 30 kilometres of total length, two (2) in the area of Thriassion plain and one (1) along the Parnitha-Krioneri-Drosia-Ekali-Dionysos axis (Attica plain) and b) 338 gravity measurements distributed along eight (8) gravity profiles, four (4) of which in Thriassion plain, three (3) in Petroupoli-Aharnes-Thrakomakedones region (Attica plain) and one (1) along Parnitha-Krioneri-Drosia-Ekali-Dionysos axis (Attica plain). Preliminary results of the geophysical investigation combined with existing geological and tectonic data are presented in this paper. Significant variation in the elevation of the alpine basement has been detected, expressed by manifestation of low and high subsurface areas which are well correlated with existing fault zones. In the area of Thriassion plain the thickness of post-alpine sediments is estimated of a few hundred meters (<500 meters) and huge thickness of several hundred meters (-800 meters) of post-alpine sediments were detected in Thrakemakedones and Krioneri areas. The relief of alpine basement is more intense in fault zones areas, such as Thriassion plain (WNW-ESE), Pathitha and Kifissos (NE-SW) as well as along the fault zone outline the Fili and Aharnes graben and is covered by postalpine formations